Formation of polymer coatings by electropolymerization - Ling, Xiaoping (University of Waterloo, 1998)
Coatings of poly(2-vinylpyridine) have been formed successfully on various substrates in aqueous medium by electropolymerization of the 2-vinylpyridine monomer. The effects of various chemical and physical variables on the electropolymerization process have been studied. These include electrolyte pH, monomer concentration, operating temperature, methanol content in the electrolyte, electrolysis duration, and nature and concentration of the supporting electrolytes. The polymer coating formed was characterized by u.v.-visible, FT-IR and ^1H NMR spectroscopies. Polymer composition, glass transition temperature and the presence o certain impurities were examined using instrumental techniques. Coating adhesion, porosity, conductivity and corrosion resistance were also evaluated. Coating thickness and surface roughness distribution were measured quantitatively using confocal scanning laser microscopy. The principal contributions of this research are the development of a successful method for the formation of poly(2-vinylpyridine) coatings via electropolymerization and the proposal of a mechanism for the process. When protonated in an acid aqueous electrolyte, 2-vinylpyridine can migrate for the process. When protonated in an acid aqueous electrolyte, 2-vinylpyridine can migrate and adsorb onto the cathodic surface during electrolysis. At a half-wave potential of -1.0 V (SCE) or more negative, the protonated 2-vinylpyridine molecules can be reduced to free-radicals which then combine with neutral formed 2-vinylpyridine molecules to form polymer chains. The polymer formed can still undergo protonation in the acidic aqueous electrolyte and be reduced at more negative electrode potentials to produce polymeric radicals. From these polymeric radicals, highly branched and crosslinked polymer chains are produced on the electrode surfaces. The value of electrolyte pH is critical to the electropolymerization process and lies in a narrow range close to the pKa value of the monomer so both protonated and neutral 2-vinylpyridine are present in sufficient amounts in the electrolyte. Cyclic potential sweep electrolysis in the range from -0.7 to -2.5 V and at a scan rate of 30 mV/s was found to be suitable for 2-vinylpyridine electropolymerization on mild steel substrates. Monomer concentrations between 0.2 and 0.3 M 2-vinylpyridine were found to produce the best coatings. A suitable range of methanol content in the electrolyte was found to be between 10 to 25 vol%. An operating temperature between 20 and 40$C was found to be most favourable for coating formation. Higher operating temperatures (> 40*C) tended to generate low molecular weight polymer, increasing the solubility of the coating polymer in the electrolyte and leading to a thin coating. The relative importance of these operating parameters decreased in the following order: monomer concentration > solution pH > methanol content in the electrolyte > operating temperature. Other operating parameters examined included electrolysis duration, which was found to affect the coating thickness proportionally during the first 2 hours, but had little effect on the coating thickness thereafter. NH4ClO4 was found to be the best supporting electrolyte for the coating formation, however, its concentration did not affect the process significantly. Poly(2-vinylpyridine) coatings have also been formed successfully on various substrates, including zinc, lead, stainless steel, copper, brass and graphite. Other monomers have been tried to form homopolymer coatings partly to test the proposed process mechanism for 2-vinylpyridine electropolymerization. This research has resolved some of the experimental discrepancies previously reported in the literature. The results and conclusions from this work should contribute significantly to the fundamental understanding of electropolymerization as well as to practical aspects of the process.
Keywords: Harvested from Collections Canada